Comprehensive Review on Phytochemicals, Pharmacological and Clinical Potentials of Gymnema sylvestre - Khan, Farzana; Sarker, Md. Moklesur Rahman; Ming, Long Chiau; Mohamed, Isa Naina; Zhao, Chao; Sheikh, Bassem Y.; Tsong, Hiew Fei; Rashid, Mohammad A. (Frontiers in Pharmacology, 2019)
Gymnema sylvestre is a plant included in Asclepiadaceae family and is located in many regions of Asia, Africa and Australia. This plant is used as a traditional therapy even now it is being used as a dietary supplement due to its numerous therapeutic potential. It is known to have sugar lowering potential in blood, thus is widely used in traditional and modern medicine system. It renders sugar lowering property due to the presence of phytochemicals such as gurmarin, gymnemic acid as well as gymnemasaponins. It is also known to have anti-oxidant, antibiotic, anti-inflammatory, antiviral, gastro and hepatoprotective, anticancer, lipid-lowering etc. activities. This review discusses in details on different pharmacological and clinical potentials of Gymnema sylvestre and its chemical constituents associated with its therapeutic potential.